CYP2B6*6 genotype specific differences in artemether‐lumefantrine disposition in healthy volunteers - Abdullahi, ST; Soyinka, JO; Olagunju, A; Bolarinwa, RA; Olarewaju, OJ; Bakare-Odunola, MT; Winterberg, M; Tarning, J; Owen, A; Khoo, S (Wiley, 2019)
Cytochrome P450 2B6 (CYP2B6) is involved in the metabolism of the antimalarial drugs artemether and lumefantrine. Here we investigated the effect of CYP2B6*6 on the plasma pharmacokinetics of artemether, lumefantrine, and their metabolites in healthy volunteers. Thirty healthy and previously genotyped adult volunteers—15 noncarriers (CYP2B6*1/*1) and 15 homozygote carriers (CYP2B6*6/*6)—selected from a cohort of 150 subjects from the Ilorin metropolitan area were administered the complete 3‐day course of artemether and lumefantrine (80 and 480 mg twice daily, respectively). Intensive pharmacokinetic sampling was conducted at different time points before and after the last dose. Plasma concentrations of artemether, lumefantrine, dihydroartemisinin, and desbutyllumefantrine were quantified using validated liquid chromatography–mass spectrometric methods. Pharmacokinetic parameters were evaluated using noncompartmental analysis. Artemether clearance of CYP2B6*6/*6 volunteers was nonsignificantly lower by 26% (ratios of geometric mean [90% CI]; 0.74 [0.52‐1.05]), and total exposure (the area under the plasma concentration‐time curve from time 0 to infinity [AUC0‐∞]) was greater by 35% (1.35 [0.95‐1.93]) when compared with those of *1/*1 volunteers. Similarly, assuming complete bioconversion from artemether, the dihydroartemisinin AUC0‐∞ was 22% lower. On the contrary, artemether‐to‐dihydroartemisinin AUC0‐∞ ratio was 73% significantly higher (1.73 [1.27‐2.37]). Comparison of lumefantrine exposure and lumefantrine‐to‐desbutyllumefantrine metabolic ratio of *6/*6 with corresponding data from *1/*1 volunteers showed no differences. The increased artemether‐to‐dihydroartemisinin metabolic ratio of *6/*6 volunteers is unlikely to result in differences in artemether‐lumefantrine efficacy and treatment outcomes. This is the first study in humans to associate CYP2B6*6 genotype with artemether disposition.